GEOMAGNETIC PALEOINTENSITY AND DIRECT AGE DETERMINATION OF THE ISEA (M0R?) CHRON - Zhu R.; Shi R.; Pan Y.; Shi G.; Hoffman K.A.; Nomade S.; Renne P.R. (My University, 2004)
A combined paleomagnetic and geochronologic study has been conducted on an andesite lava sequence at Jianguo (Liaoning province, northeastern China). Thermal demagnetization and thermomagnetic analysis revealed that natural remanent magnetization is carried by both magnetite and hematite. Stepwise thermal demagnetization up to 675°C isolated well-defined reverse characteristic remanent magnetization (ChRM) in three time-independent lava flows with a mean direction of D/I=179.2°/−59.7° with α95=3.0°. It also showed that a high-temperature component (>585°C) has the same ChRM direction as that of the low- to medium-temperature (ca. 170/300–585°C) components. A modified version of the Thellier–Thellier paleointensity method [Coe, J. Geophys. Res. 72 (1967) 3247–3262] with systematic partial thermoremanent magnetization checks was used for paleointensity determinations. Twelve out of 39 samples yielded reliable results in the temperature interval of 170–550°C. Virtual dipole moment values range from 3.9 to 4.7×1022 Am2 with an average of 4.2±0.1×1022 Am2. 40Ar/39Ar age determination on one lava flow is 116.8±3.0 Myr (2σ error, relative to Fish Canyon sanidine: 28.02±0.28 Myr). The magnetic reversed polarity with well-defined age could correspond to the ‘ISEA’ within the older part of the Cretaceous normal superchron (CNS), but we cannot rule out the possibility that this reversal interval could also correspond to the M0r due to many ambiguities on previous published ages on ISEA and M0r intervals as well as the new monitor age correction we applied. It also suggests that a weak magnetic field nature already documented before the CNS extended at least into the very beginning of the CNS.